Autenticação de orégano (origanum vulgare l.) orgânico empregando espectroscopia e quimiometria - Fernandez, Ana Sophia Tovar (2020)
In recent years, consumption of organic foods has considerably increased. The difference between organic and conventional food products is the way they are produced and processed. In general, organic foods are characterized by their restriction on the use of pesticides and synthetic fertilizers in their cultivation. Thus, foods labeled organic should not contain residues of synthetic fertilizers, chemical pesticides, genetically modified organisms, hormones and antibiotics. Oregano is a spice known for its characteristic aroma and one of the most popular condiments in the world, receiving prominence for its antimicrobial, antioxidant and antiinflammatory properties. The authenticity of organic foods is a current concern in the food industry. In this sense, the objective of this work was to propose an analytical methodology based on near- infrared spectroscopy (NIR) region in conjunction with the partial least squares tool with discriminant analysis (PLS-DA) for authentication of Origanum vulgare L. (oregano) organic. A total of 140 samples (50 organic and 90 non-organic) were evaluated using NIR spectroscopy in reflectance mode. The granulometry was standardized in 60 mesh. The spectra were pre-processed through smoothing and first derivative. The PLS-DA supervised model was built with data centered on the mean, using 2 latent variables. The distribution of the calibration and validation samples in the organic and non-organic classes resulted in a clear separation. In the constructed model, the sensitivity and specificity for the organic and non-organic classes were equal to 1. This means that the model was able to correctly classify all samples in their respective class. As a result, the NIR spectroscopy associated with the PLS-DA chemometric tool was able to authenticate samples of organic and non-organic oregano. In addition, the NIR / PLS-DA was able to promote a rapid and non-destructive analysis in the authentication of organic samples. Important spectral regions for this authentication were highlighted by (VIP) scores being from the importance of the variables in the (VIP) projection from 1350 to 1430 nm, and from 1450 to 1480 nm, where it is observed absorption due to ROH, ArOH, CONH2, RNH2, COHR, CH, CH2 and CH3.